Re-Os isotope and highly siderophile element systematics of the Parana continental flood basalts (Brazil) - Rocha-Junior, Eduardo R. V.; Puchtel, Igor S.; Marques, Leila S.; Walker, Richard J.; Machado, Fabio B.; Nardy, Antonio J. R. [UNESP]; Babinski, Marly; Figueiredo, Ana M. G. (Elsevier B.V., 2012)
Basalts of the Parana continental flood basalt (PCFB) province erupted through dominantly Proterozoic continental crust during the Cretaceous. In order to examine the mantle source(s) of this major flood basalt province, we studied Os, Sr, Nd, and Pb isotope systematics, and highly siderophile element (HSE) abundances in tholeiitic basalts that were carefully chosen to show the minimal effects of crustal contamination. These basalts define a precise Re-Os isochron with an age of 131.6 +/- 2.3 Ma and an initial Os-187/Os-188 of 0.1295 +/- 0.0018 (gamma Os-187 = +2.7 +/- 1.4). This initial Os isotopic composition is considerably more radiogenic than estimates of the contemporary Depleted Mantle (DM). The fact that the Re-Os data define a well constrained isochron with an age similar to Ar-40/Ar-39 age determinations, despite generally low Os concentrations, is consistent with closed-system behavior for the HSE. Neodymium, Sr, and Pb isotopic data suggest that the mantle source of the basalts had been variably hybridized by melts derived from enriched mantle components. To account for the combined Os, Nd, Sr, and Pb isotopic characteristics of these rocks, we propose that the primary melts formed from metasomatized asthenospheric mantle (represented by arc-mantle peridotite) that underwent mixing with two enriched components, EM-I and EM-II. The different enriched components are reflected in minor isotopic differences between basalts from southern and northern portions of the province.The Tristan da Cunha hotspot has been previously suggested to be the cause of the Parana continental flood basalt magmatism. However, present-day Tristan da Cunha lavas have much higher Os-187/Os-188 isotopic compositions than the source of the PCFB. These data, together with other isotopic and elemental data, preclude making a definitive linkage between the Tristan plume and the PCFB. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Parana continental flood basalts; Re-Os isotopic systematics; Tristan da Cunha; highly siderophile elements; mantle plume